Assessment of Pruritus in Feline Dermatological Affections using Trichogram and Predesigned Scoring Systems - A Preliminary Study - Mathai, Varsha Mary; Sarangom, Sherin B; K, Roshna (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The study was undertaken to identify the common dermatological conditions of cats, to evaluate their clinical status and to study pruritus using predesigned scoring system and trichogram. A total of 250 client owned cats were selected randomly irrespective of the presence or absence of apparent pruritus or skin lesions. Of these, 129 (51.6%) cats were diagnosed as dermatological case. Out of 129 cases, 52 (40.31%) were positive for Lynxacarus radovskyi, 37 (28.68%) Otodectes cynotis, 15 (11.63%) Ctenocephalides felis, 8 (6.20%) Felicola subrostratus, 4 (3.10%) Sarcoptes sp., 9 (6.98%) Malassezia sp., 3 (2.33%) pyoderma and 1 (0.77%) Demodex gatoi. Pruritus was the most observable and earliest clinical sign in most of the dermatological conditions. In each of the 129 cases, pruritus was retrospectively graded using a predesigned 5-point numerical scale and trichogram analysis. Out of 129 cats positive for various skin conditions, mostly due to ectoparasites, 23 (17.83 %) cats had pruritus score zero. In 96.1% (124/129) cats with various condition, trichogram analysis of 100 hair tips in each case revealed moderate (50-70%) to large (>70%) proportions of blunt or frayed hair tips. Out of 23 cats with pruritus score zero, 18 cats had moderate proportions (50-70%) of damaged hair tips on trichogram. The existence of feline population infested with ectoparasites that showed subtle signs or no signs of pruritus may evade veterinary intervention through under-diagnosis and further spread the vector borne diseases to other animals and humans.